SENSORIAMENTO REMOTO PERMITE ESTIMAR O DÉFICIT HÍDRICO E PERDAS DE RENDIMENTO EM CULTIVARES DE FEIJÃO - Alves, Daniel Soares; Nitsche, Pablo Ricardo; Cirino, Vania Moda; Scholz, Maria Brigida dos Santos; Neto, José dos Santos; Caramori, Paulo Henrique (IRRIGA, 2021)
REMOTE SENSING ALLOWS TO ESTIMATE WATER STRESS AND YIELD LOSSES OF BEAN CULTIVARS DANIEL SOARES ALVES1; PABLO RICARDO NITSCHE1; VANIA MODA CIRINO2; MARIA BRIGIDA DOS SANTOS SCHOLZ1; JOSÉ DOS SANTOS NETO2 E PAULO HENRIQUE CARAMORI1 1 Área de Agrometeorologia, Ecofisiologia e Tecnologia de Alimentos, Instituto de Desenvolvimento Rural do Paraná IAPAR – EMATER, Rod. Celso Garcia Cid, 375, Conjunto Ernani Moura Lima II, 86.047 – 902, Londrina, Paraná, Brasil. danielsoares@idr.pr.gov.br; pablo.nitsche@idr.pr.gov.br; mbscholz@iapar.br; pcaramori@gmail.com 2 Área de Melhoramento e Propagação Vegetal, Instituto de Desenvolvimento Rural do Paraná IAPAR – EMATER, Rod. Celso Garcia Cid, 375, Conjunto Ernani Moura Lima II, 86.047 – 902, Londrina, Paraná, Brasil. vamoci@idr.pr.gov.br ; js.neto@idr.pr.gov.br 1 ABSTRACT Reflectance measurements can indicate the physiological quality of plants and contribute to the correct differentiation of cultivars. Here, we studied the spectral responses at wavelengths of 410–810 nm of four common bean (Phaseolus vulgaris) cultivars subjected to water stress in the flowering stage at the Rural Development Institute of Paraná in Londrina, in the state of Paraná, Brazil. The reflectance values presented differences among the water regimes treatments at the wavelengths studied. For plants without water stress, it was possible to distinguish between IPR Andorinha and IPR Colibri cultivars using wavelengths of 460 and 760 nm, respectively. With a wavelength of 810 nm, there was a differentiation among IPR Andorinha (reflectance of 25.13%), IAC Imperador (23.51%), and IPR Colibri (21.92%) cultivars; however, the latter was not significantly different from the IPR Curió (22.26%) cultivar. The highest correlations with yield (R2 > 0.90) occurred at wavelengths of 460, 510, 560, 610, and 710 nm. The water treatments increased the protein content only for IPR Andorinha cultivars. It is concluded that the spectral response correlates with productivity and makes it possible to identify the water status of bean cultivars. This demonstrates that remote sensing techniques can be used to identify water stress in this crop. Keywords: irrigation, Phaseolus vulgaris, reflectance, drought. ALVES, D. S.; NITSCHE, P. R.; CIRINO, V. M; SCHOLZ, M. B. S; NETO, J. D. S; CARAMORI, P. H. SENSORIAMENTO REMOTO PERMITE ESTIMAR O DÉFICIT HÍDRICO E PERDAS DE RENDIMENTO EM CULTIVARES DE FEIJÃO 2 RESUMO Medidas de reflectância podem indicar a qualidade fisiológica das plantas e contribuir para a correta diferenciação de cultivares. Estudou-se a resposta espectral, nos comprimentos de onda (λ) de 410 a 810 nm, em quatro cultivares de feijão (Phaseolus vulgaris) submetidas ao déficit hídrico no florescimento, no Instituto de Desenvolvimento Rural do Paraná, em Londrina – PR. A reflectância foi distinta entre os regimes hídricos em todos os comprimentos de onda (λ). Nos tratamentos sem déficit hídrico foi possível diferenciar as cultivares IPR Andorinha e IPR Colibri com λ de 460 nm e 760 nm, respectivamente. Com λ de 810 nm, houve diferenciação entre as cultivares IPR Andorinha (reflectância de 25,13%), IAC Imperador (23,51%) e IPR Colibri (21,92%), esta última sem diferença significativa com a cultivar IPR Curió (22,26%). As maiores correlações com a produtividade (R2 > 0,90) ocorreram com λ de 460, 510, 560, 610 e 710nm. Os tratamentos hídricos promoveram aumento no teor de proteína apenas para a cultivar IPR Andorinha. Conclui-se que a resposta espectral se correlaciona com a produtividade e possibilita identificar o status hídrico de cultivares de feijão. Isto permite o uso das técnicas de sensoriamento remoto como ferramenta auxiliar na identificação de estresse hídrico na cultura. Palavras-chave: irrigação, Phaseolus vulgaris, reflectância, seca.